Adhesive sheet

By adding specific amounts of Na ions and/or K ions to the water-dispersed adhesive composition in adhesive sheets, the water resistance of the adhesive layer is enhanced, addressing the issue of reduced peel strength under wet and heat conditions.

JP7663320B2Active Publication Date: 2025-04-16NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020038907
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-06
Publication Date
2025-04-16
Estimated Expiration
2040-03-06

AI Technical Summary

Technical Problem

Water-dispersed adhesive compositions used in adhesive sheets often suffer from reduced water resistance, particularly when containing tackifying resin emulsions, as they tend to lose peel strength under wet and heat conditions.

Method used

Incorporating specific amounts of Na ions and/or K ions into the water-dispersed adhesive composition, which includes an acrylic polymer and a water-dispersed tackifying resin, enhances the water resistance of the adhesive layer. The total content of Na ions and K ions should be between 0.3 parts by weight and 0.8 parts by weight per 100 parts by weight of the adhesive sheet.

Benefits of technology

The addition of Na ions and/or K ions significantly improves the water resistance of the adhesive layer, maintaining peel strength even under conditions of heat and humidity, thereby enhancing the adhesive sheet's performance in wet environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663320000002
    Figure 0007663320000002
  • Figure 0007663320000001
    Figure 0007663320000001
Patent Text Reader

Abstract

To provide an adhesive sheet including an adhesive layer exhibiting improved water resistance.SOLUTION: An adhesive sheet 1 includes an adhesive layer formed of a water-dispersed adhesive composition. The water-dispersed adhesive composition contains an acrylic polymer as a base polymer, a water-dispersed tackifier resin, and at least one kind of Na ions and K ions. The total amount of Na ions and K ions contained in the adhesive sheet is 0.3 pt.wt. or more and 0.8 pt.wt. or less per 100 pts.wt. of the adhesive sheet.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed using a water-dispersed pressure-sensitive adhesive composition. [Background technology]

[0002] A water-dispersed pressure-sensitive adhesive composition in a form containing a dispersed pressure-sensitive adhesive component in an aqueous medium (an emulsion-type pressure-sensitive adhesive composition in which the pressure-sensitive adhesive component is dispersed in an aqueous medium) is more desirable from the viewpoint of environmental hygiene than a pressure-sensitive adhesive composition in a form in which the pressure-sensitive adhesive component is dissolved in an organic solvent (a solvent-type pressure-sensitive adhesive composition). For this reason, pressure-sensitive adhesive sheets made using the water-dispersed pressure-sensitive adhesive composition are used in various fields in the form of double-sided tapes and the like. Patent Document 1 is an example of a technical document relating to a water-dispersed pressure-sensitive adhesive composition. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-132993 A Summary of the Invention [Problem to be solved by the invention]

[0004] A tackifier resin may be blended into the pressure-sensitive adhesive composition for the purpose of improving peel strength, etc. The tackifier resin is generally water-insoluble, and therefore in the case of a water-dispersed pressure-sensitive adhesive composition, the tackifier resin is often used in the form of a tackifier resin emulsion (water-dispersed tackifier resin) in which the tackifier resin is dispersed in water. However, when a water-dispersed pressure-sensitive adhesive composition contains a tackifier resin emulsion, the water resistance (e.g., the ability to maintain peel strength when held under moist heat conditions) of the pressure-sensitive adhesive layer formed from the composition tends to decrease.

[0005] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a pressure-sensitive adhesive sheet including a pressure-sensitive adhesive layer that exhibits improved water resistance. [Means for solving the problem]

[0006] The present inventors have discovered that in a pressure-sensitive adhesive sheet including a pressure-sensitive adhesive layer, when a water-dispersible pressure-sensitive adhesive composition containing an acrylic polymer as a base polymer and a water-dispersible tackifier resin contains a specific amount of Na ions and / or K ions, the effect of significantly improving the water resistance of the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition is exerted, and have completed the present invention.

[0007] According to this specification, a pressure-sensitive adhesive sheet is provided that includes a pressure-sensitive adhesive layer formed from a water-dispersed pressure-sensitive adhesive composition. The water-dispersed pressure-sensitive adhesive composition includes an acrylic polymer as a base polymer, a water-dispersed tackifier resin, and at least one of Na ions and K ions. The total amount of Na ions and K ions contained in the pressure-sensitive adhesive sheet is 0.3 parts by weight or more and 0.8 parts by weight or less per 100 parts by weight of the pressure-sensitive adhesive sheet.

[0008] In this way, by incorporating Na ions and / or K ions in a water-dispersible PSA composition that uses an acrylic polymer as the base polymer and contains a water-dispersible tackifier resin such that the total content of Na ions and K ions is from 0.3 to 0.8 parts by weight per 100 parts by weight of the PSA sheet, the water resistance of the PSA layer formed from the PSA composition can be significantly improved.

[0009] The acrylic polymer is preferably a polymer (typically an emulsion polymer) of a monomer raw material containing more than 50% by weight of alkyl (meth)acrylate. An acrylic water-dispersed pressure-sensitive adhesive composition containing such an acrylic polymer as a base polymer can easily provide a pressure-sensitive adhesive sheet including a pressure-sensitive adhesive layer exhibiting good adhesive properties.

[0010] The aqueous dispersion-type PSA composition disclosed herein preferably contains a surfactant. The use of a surfactant makes it easier to obtain an PSA sheet including a PSA layer that exhibits improved water resistance. The aqueous dispersion-type PSA composition according to a preferred embodiment contains a reactive surfactant as the surfactant. The use of a reactive surfactant makes it easier to obtain an PSA sheet including a PSA layer that exhibits higher water resistance.

[0011] The content of the water-dispersible tackifier resin can be, for example, 1 part by weight or more and 70 parts by weight or less relative to 100 parts by weight of the base polymer. A water-dispersible PSA composition having such a composition can easily provide a PSA sheet including a PSA layer that preferably exhibits both good water resistance and adhesive properties.

[0012] In another preferred embodiment of the technology disclosed herein, the water-dispersible tackifier resin contains a tackifier resin having a softening point of 90° C. or higher. Using a tackifier resin with a high softening point can be advantageous in terms of the cohesiveness of the adhesive. Thus, a configuration containing a tackifier resin with a high softening point makes it easier to obtain a pressure-sensitive adhesive sheet containing a pressure-sensitive adhesive layer with excellent adhesive properties.

[0013] A pressure-sensitive adhesive sheet according to a preferred embodiment has a 180-degree peel strength of 4 N / 20 mm or more after being attached to a stainless steel plate and held for 24 hours under conditions of 60°C and 95% RH (hereinafter also referred to as "after heating and humidification"). A pressure-sensitive adhesive sheet that exhibits the above peel strength after heating and humidification is preferably used as a pressure-sensitive adhesive sheet with good water resistance.

[0014] In another preferred embodiment of the pressure-sensitive adhesive sheet, the 180° peel strength after being attached to a stainless steel plate and kept at 60° C. and 95% RH for 24 hours is at least 0.5 times the 180° peel strength after being attached to a stainless steel plate and kept at 23° C. and 50% RH for 30 minutes. Thus, a pressure-sensitive adhesive sheet having a high peel strength retention rate against heating and humidification (hereinafter also simply referred to as "retention rate") is preferably used as a pressure-sensitive adhesive sheet with good water resistance.

[0015] A preferred embodiment of the pressure-sensitive adhesive sheet is configured as a double-sided pressure-sensitive adhesive sheet including a substrate and, as the pressure-sensitive adhesive layer, a first pressure-sensitive adhesive layer disposed on one surface of the substrate and a second pressure-sensitive adhesive layer disposed on the other surface of the substrate. The double-sided pressure-sensitive adhesive sheet having the above configuration is preferably used for bonding various articles and members. The pressure-sensitive adhesive sheet disclosed herein can be preferably implemented, for example, in an embodiment in which the substrate is a nonwoven fabric. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a configuration of a pressure-sensitive adhesive sheet according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] A preferred embodiment of the present invention will be described below. Note that matters other than those specifically mentioned in this specification and necessary for carrying out the present invention can be understood by a person skilled in the art based on the teachings on carrying out the invention described in this specification and the common general knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general knowledge in the field. In addition, in the following drawings, components and parts having the same function may be described by using the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments described in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the product actually provided.

[0018] In this specification, the term "adhesive" refers to a material that exhibits a soft solid (viscoelastic) state at temperatures around room temperature and has the property of adhering to an adherend by pressure. The adhesive referred to here is generally a material having a complex tensile modulus E * (1Hz)<10 7 dyne / cm 2(typically, a material having the above properties at 25° C.) The adhesive in the technology disclosed herein can also be understood as the solid content (non-volatile content) of the adhesive composition or a constituent of the adhesive layer.

[0019] In this specification, "(meth)acryloyl" refers collectively to acryloyl and methacryloyl. Similarly, "(meth)acrylate" refers collectively to acrylate and methacrylate, and "(meth)acrylic" refers collectively to acrylic and methacrylic.

[0020] In this specification, the term "acrylic polymer" refers to a polymer containing more than 50% by weight of monomer units derived from an acrylic monomer as monomer units constituting the polymer. The acrylic monomer refers to a monomer derived from a monomer having at least one (meth)acryloyl group in one molecule.

[0021] In this specification, "water-dispersed" means a form in which at least a part of the components are dispersed in water. For example, "water-dispersed PSA composition" means a composition that contains a PSA composition and water, and at least a part of the PSA composition is dispersed in water. The water-dispersed type also includes a suspended state and an emulsified state.

[0022] <Water-dispersible pressure-sensitive adhesive composition> The PSA composition disclosed herein is an aqueous dispersion type (typically, aqueous emulsion type) PSA composition in which an adhesive component is dispersed in an aqueous medium. The aqueous medium herein means that the solvent constituting the medium is water or a mixed solvent (aqueous solvent) mainly composed of water.

[0023] (Acrylic polymer) The adhesive composition disclosed herein is an acrylic adhesive composition containing an acrylic polymer as a base polymer. Here, the term "base polymer" refers to a main component among the polymer components contained in the adhesive composition (which may also be an adhesive). In addition, in this specification, the term "main component" refers to a component contained in an amount of more than 50% by weight, unless otherwise specified. In a preferred embodiment, the acrylic adhesive composition is an acrylic emulsion-type adhesive composition containing a water-dispersed acrylic polymer. The water-dispersed acrylic polymer has an emulsion form in which the acrylic polymer is dispersed in water. As such an acrylic polymer, one having an alkyl (meth)acrylate as a main constituent monomer component (monomer main component, i.e., a component that accounts for more than 50% by weight of the total amount of monomers constituting the acrylic polymer) can be preferably used.

[0024] Acrylic polymers include, for example, polymers having alkyl (meth)acrylate as the main monomer. and a monomer raw material which may further contain a sub-monomer copolymerizable with the main monomer ( The main monomer is preferably a polymer of the monomer component. This refers to a component that accounts for more than 50% by weight of the monomer composition.

[0025] As the alkyl (meth)acrylate, for example, a compound represented by the following formula (1) is preferable. can be used. CH2=C(R 1 )COOR 2 (1) Here, R in the above formula (1) 1 is a hydrogen atom or a methyl group. 2 is a chain alkyl group having 1 to 20 carbon atoms (hereinafter, this range of carbon atoms is referred to as "C 1-20 From the viewpoint of the storage modulus of the adhesive, R 2 C 1-14 Preferred is alkyl (meth)acrylate, which is a chain alkyl group represented by the formula R 2 C 1-10More preferred is an alkyl (meth)acrylate having a chain alkyl group represented by the formula R 2 Particularly preferred are alkyl (meth)acrylates in which is a butyl group or a 2-ethylhexyl group.

[0026] R 2 C 1-20 Examples of alkyl(meth)acrylates, which are chain alkyl groups, include methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, isopropyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, s-butyl(meth)acrylate, pentyl(meth)acrylate, isopentyl(meth)acrylate, hexyl(meth)acrylate, heptyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, octyl(meth)acrylate, and isooctyl(meth)acrylate. Examples of the alkyl (meth)acrylate include butyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. These alkyl (meth)acrylates can be used alone or in combination of two or more. Examples of preferred alkyl (meth)acrylates include n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA).

[0027] The technology disclosed herein is characterized in that the monomer component is R 2 C 4-10 Among the alkyl (meth)acrylates contained in the monomer component, R 2 C 4-10This can be preferably implemented in an embodiment in which the total amount of alkyl (meth)acrylate, which is a chain alkyl group (typically the total amount of BA and 2EHA), is 70% by weight or more (typically 80% by weight or more).

[0028] The alkyl (meth)acrylate is represented by the formula (1) R 2 C 4-10 In the case where the alkyl (meth)acrylate (typically at least one of BA and 2EHA) is a chain alkyl group represented by the formula (1), other alkyl (meth)acrylates (R 2 is less than C4 or C 10 The total amount of the alkyl(meth)acrylates (which are chain alkyl groups of more than 100 nm) in the monomer components constituting the acrylic polymer is preferably about 30% by weight or less (e.g., 20% by weight or less, typically 15% by weight or less). From the viewpoint of obtaining the effect of the other alkyl(meth)acrylates, the total amount is preferably about 1% by weight or more (e.g., 5% by weight or more, typically 10% by weight or more) in the monomer components. The other alkyl(meth)acrylates include those represented by the formula (1) R 2 C 1-3 Preferably, alkyl(meth)acrylates, which are chain alkyl groups, are used. Specific examples include methyl acrylate (MA), methyl methacrylate (MMA), ethyl acrylate (EA), etc. Among these, MA is more preferred.

[0029] The secondary monomers copolymerizable with the main monomer alkyl (meth)acrylate can be useful for introducing crosslinking points into the acrylic polymer and for increasing the cohesive strength of the acrylic polymer. As the secondary monomers, for example, the following functional group-containing monomer components can be used alone or in combination of two or more. Carboxyl group-containing monomers: for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), crotonic acid, etc.; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, citraconic acid, etc., and their anhydrides (maleic anhydride, itaconic anhydride, etc.). Hydroxyl group-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, etc.; unsaturated alcohols such as vinyl alcohol, allyl alcohol, etc. Amide group-containing monomers: for example, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide. Amino group-containing monomers: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, t-butylaminoethyl (meth)acrylate. Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether. Cyano group-containing monomers: for example acrylonitrile, methacrylonitrile. Keto group-containing monomers: for example, diacetone (meth)acrylamide, diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, vinyl acetoacetate. Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acryloylmorpholine. Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane.

[0030] The functional group-containing monomers can be used alone or in combination of two or more. Among the functional group-containing monomers, carboxyl group-containing monomers, hydroxyl group-containing monomers, and cyano group-containing monomers are preferred, and carboxyl group-containing monomers are more preferred, because they can favorably realize the introduction of crosslinking points and the improvement of cohesive force as described above. Among the carboxyl group-containing monomers, AA and MAA are preferred.

[0031] In a preferred embodiment, AA and MAA are used in combination as the functional group-containing monomer. A pressure-sensitive adhesive composition containing an acrylic polymer of such a monomer composition (i.e., copolymer composition) can provide a pressure-sensitive adhesive sheet with higher performance (for example, better repulsion resistance). The weight ratio of AA to MAA (AA / MAA) can be, for example, in the range of about 0.1 to 10, more preferably about 0.3 or more (typically 0.5 or more), and more preferably about 5 or less (typically 4 or less). By having AA / MAA in the above range, there is a tendency that the effect of improving repulsion resistance is easily obtained sufficiently, and after the pressure-sensitive adhesive sheet is produced, there is a tendency that the adhesive properties tend to have excellent stability over time.

[0032] In addition, it is preferable that an alkoxysilyl group-containing monomer is copolymerized in the acrylic polymer. The alkoxysilyl group-containing monomer is typically an ethylenically unsaturated monomer having at least one alkoxysilyl group (preferably two or more, for example, two or three) in one molecule, and specific examples thereof are as described above. The above alkoxysilyl group-containing monomer can be used alone or in combination of two or more. By copolymerizing the alkoxysilyl group-containing monomer, a crosslinked structure due to a condensation reaction of a silanol group (silanol condensation) can be introduced into the adhesive formed from the adhesive composition containing the acrylic polymer.

[0033] When a functional group-containing monomer is copolymerized in an acrylic polymer, the ratio of the functional group-containing monomer to the total monomer components constituting the acrylic polymer is not particularly limited. In general, from the viewpoint of achieving a good balance between cohesive strength and adhesiveness, it is preferable to set the ratio of the functional group-containing monomer to about 0.1% by weight or more (e.g., 0.5% by weight or more, typically 1% by weight or more). In addition, taking into account the adhesive effect of alkyl (meth)acrylate, it is preferable to set the ratio to about 40% by weight or less (e.g., 30% by weight or less, typically 20% by weight or less). When a carboxyl group-containing monomer is copolymerized with an acrylic polymer, the proportion of the carboxyl group-containing monomer in the total monomer components is suitably 15% by weight or less from the viewpoint of improving water resistance, and may be, for example, 10% by weight or less, 5% by weight or less, or 3% by weight or less. On the other hand, from the viewpoint of cohesion and the like, in some embodiments, the proportion may be, for example, 0.1% by weight or more, or 0.5% by weight or more. According to the technology disclosed herein, good water resistance can be achieved even in an embodiment in which the proportion of the carboxyl group-containing monomer in the total monomer components is 1% by weight or more, or 1.5% by weight or more. When an alkoxysilyl group-containing monomer is copolymerized into an acrylic polymer, the proportion of the alkoxysilyl group-containing monomer in the total monomer components is suitably 0.005% by weight or more (e.g., 0.01% by weight or more) and suitably about 0.1% by weight or less (e.g., 0.03% by weight or less) of the total monomer components.

[0034] In addition, for the purpose of increasing the cohesive strength of the acrylic polymer, other copolymerization components can be used in addition to the above-mentioned secondary monomers. Examples of such copolymerization components include vinyl ester monomers such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene, substituted styrenes (α-methylstyrene, etc.) and vinyl toluene; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate and isobornyl (meth)acrylate; aryl (meth)acrylates (e.g., phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), arylalkyl (meth)acrylates (e.g., phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), arylalkyl (meth)acrylates (e.g., phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), aryloxy ...phenoxyethyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl ( aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate; olefin-based monomers such as ethylene, propylene, isoprene, butadiene, isobutylene; chlorine-containing monomers such as vinyl chloride, vinylidene chloride; isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate; vinyl ether-based monomers such as methyl vinyl ether, ethyl vinyl ether; and the like.

[0035] Other examples of copolymerizable components other than the above-mentioned secondary monomers include monomers having a plurality of functional groups in one molecule. Examples of such polyfunctional monomers include 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, glycerin di(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, divinylbenzene, butyl di(meth)acrylate, hexyl di(meth)acrylate, and the like.

[0036] The amount of copolymerization components other than the above-mentioned secondary monomers may be appropriately selected depending on the purpose and application, and is not particularly limited. For example, it is preferably 10% by weight or less of the monomer composition of the acrylic polymer.

[0037] The acrylic polymer in the technology disclosed herein is suitably designed so that the glass transition temperature (Tg) of the polymer is −25° C. or lower (typically −75° C. or higher and −25° C. or lower). The Tg of the acrylic polymer may be preferably −40° C. or lower (e.g., −70° C. or higher and −40° C. or lower), more preferably −50° C. or lower (typically −70° C. or higher and −50° C. or lower). It is preferable to set the Tg of the acrylic polymer to the above-mentioned upper limit value or lower from the viewpoint of improving adhesive strength. The Tg of the acrylic polymer can be adjusted by the type and amount ratio of the monomers used in the synthesis of the polymer.

[0038] Here, the Tg of an acrylic polymer refers to the Tg calculated by the Fox formula based on the composition of the monomer components used in the synthesis of the polymer. The Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(Wi / Tgi) In the above Fox formula, Tg represents the glass transition temperature (unit: K) of the copolymer, Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio on a weight basis), and Tgi represents the glass transition temperature (unit: K) of the homopolymer of monomer i.

[0039] The glass transition temperature of the homopolymer used to calculate Tg is a value described in a publicly known document. For example, for the monomers listed below, the following values ​​are used as the glass transition temperatures of the homopolymers of the monomers. 2-Ethylhexyl acrylate -70℃ n-Butyl acrylate -55℃ Methyl methacrylate 105℃ Methyl acrylate 8℃ Vinyl acetate 32℃ Acrylic acid 106℃ Methacrylic acid 228℃

[0040] For the glass transition temperatures of homopolymers of monomers other than those listed above, the values ​​given in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989) shall be used. When multiple values ​​are given in this document, the highest value shall be used.

[0041] For monomers for which the glass transition temperature of the homopolymer is not described in the Polymer Handbook, the value obtained by the following measurement method shall be used (see JP 2007-51271 A). Specifically, 100 parts by weight of monomer, 0.2 parts by weight of azobisisobutyronitrile, and 200 parts by weight of ethyl acetate as a polymerization solvent are charged into a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser, and stirred for 1 hour while passing nitrogen gas through. After removing oxygen from the polymerization system in this way, the temperature is raised to 63°C and reacted for 10 hours. Then, the mixture is cooled to room temperature to obtain a homopolymer solution with a solid concentration of 33% by weight. Then, the homopolymer solution is cast and applied onto a release liner, and dried to prepare a test sample (sheet-shaped homopolymer) with a thickness of about 2 mm. This test sample was punched out into a disk with a diameter of 7.9 mm, sandwiched between parallel plates, and subjected to a shear strain of 1 Hz using a viscoelasticity tester (ARES, Rheometrics Corporation). Viscoelasticity was measured in shear mode at a temperature range of -70 to 150°C and a heating rate of 5°C / min. The peak top temperature of tan δ was taken as the Tg of the homopolymer.

[0042] The method for obtaining an acrylic polymer is not particularly limited, and various polymerization methods known as synthesis methods for acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization, can be appropriately adopted. An example of a polymerization method that can be preferably adopted is emulsion polymerization. The mode of emulsion polymerization is not particularly limited, and various monomer supply methods, polymerization conditions, materials used, etc. similar to those of conventionally known general emulsion polymerization can be appropriately adopted. For example, as a monomer supply method, a batch charging method in which all monomer raw materials are supplied at once, a continuous supply (dropping) method, a divided supply (dropping) method, etc. can be appropriately adopted. The monomer raw materials may be dropped in the form of an aqueous emulsion. The polymerization temperature can be, for example, about 20°C or higher (usually 40°C or higher), and is suitably about 100°C or lower (usually 80°C or lower).

[0043] According to the emulsion polymerization, a polymerization liquid (acrylic polymer emulsion) in the form of an emulsion in which an acrylic polymer is dispersed in water can be prepared. The water-dispersed pressure-sensitive adhesive composition disclosed herein can be preferably produced using the polymerization liquid or the polymerization liquid that has been subjected to an appropriate post-treatment. Alternatively, an acrylic polymer may be synthesized using a polymerization method other than emulsion polymerization (e.g., solution polymerization, photopolymerization, bulk polymerization, etc.), and the polymer may be dispersed in water to prepare an acrylic polymer emulsion.

[0044] The initiator used in the polymerization can be appropriately selected from conventionally known polymerization initiators depending on the type of polymerization method, such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, etc. Examples of the polymerization initiator include, but are not limited to, azo-based initiators such as potassium persulfate and ammonium persulfate; peroxide-based initiators such as benzoyl peroxide, t-butyl hydroperoxide, and hydrogen peroxide; substituted ethane-based initiators such as phenyl-substituted ethane; carbonyl-based initiators such as aromatic carbonyl compounds; and redox-based initiators such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peroxide and sodium ascorbate. Such polymerization initiators can be used alone or in combination of two or more.

[0045] The amount of the polymerization initiator used is not particularly limited as long as it is a normal amount. For example, it can be selected from the range of about 0.005 parts by weight or more (preferably 0.01 parts by weight or more) and about 1 part by weight or less (preferably 0.8 parts by weight or less) relative to 100 parts by weight of the total monomer components.

[0046] During polymerization, a chain transfer agent (which may also be understood as a molecular weight regulator or polymerization degree regulator) may be used as necessary. Examples of the chain transfer agent include mercaptans such as dodecyl mercaptan (dodecanethiol), lauryl mercaptan, glycidyl mercaptan, 2-mercaptoethanol, mercaptoacetic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol, as well as α-methylstyrene dimer. Such chain transfer agents may be used alone or in combination of two or more.

[0047] The amount of the chain transfer agent used can be about 0.001 parts by weight or more (typically about 0.005 parts by weight or more, for example about 0.001 parts by weight or more) relative to 100 parts by weight of the monomer component, and can be, for example, about 5 parts by weight or less (typically about 2 parts by weight or less, for example about 1 part by weight or less). By setting the amount of the chain transfer agent used in an appropriate range, a desired polymerization rate can be obtained.

[0048] Emulsion polymerization of monomer raw materials is usually carried out in the presence of a surfactant (emulsifier). The amount of surfactant used is not particularly limited. In consideration of polymerization stability and dispersion stability of the polymerization reaction product, the amount of surfactant used is usually 0.1 parts by weight or more relative to 100 parts by weight of monomer raw materials, and preferably 0.5 parts by weight or more. From the viewpoint of obtaining higher stability, it may be 1.0 parts by weight or more, or may be 1.5 parts by weight or more. In addition, the amount of surfactant used may be, for example, 10 parts by weight or less relative to 100 parts by weight of monomer raw materials. On the other hand, from the viewpoint of improving water resistance, it is desirable to suppress the amount of surfactant used (especially non-reactive surfactant). From such a viewpoint, the amount of surfactant used is usually preferably 5 parts by weight or less, may be 4 parts by weight or less, may be 3 parts by weight or less, or may be 2.5 parts by weight or less.

[0049] As the surfactant, known anionic surfactants, nonionic surfactants, cationic surfactants, etc. can be used. Usually, anionic or nonionic surfactants are preferred. Surfactants having reactive functional groups (typically radically polymerizable functional groups) may be used. Hereinafter, surfactants having reactive functional groups are referred to as reactive surfactants, whereas general surfactants not having reactive functional groups may be referred to as non-reactive surfactants. The surfactants may be used alone or in combination of two or more.

[0050] Examples of non-reactive anionic surfactants include alkyl sulfates such as lauryl sulfate and octadecyl sulfate; fatty acid salts; alkyl benzene sulfonates such as nonyl benzene sulfonate and dodecyl benzene sulfonate; naphthalene sulfonates such as dodecyl naphthalene sulfonate; alkyl diphenyl ether disulfonates such as dodecyl diphenyl ether disulfonate; polyoxyethylene alkyl ether sulfates such as polyoxyethylene octadecyl ether sulfate and polyoxyethylene lauryl ether sulfate; polyoxyethylene alkyl phenyl ether sulfates such as polyoxyethylene lauryl phenyl ether sulfate; polyoxyethylene styrenated phenyl ether sulfate; sulfosuccinates such as lauryl sulfosuccinate and polyoxyethylene lauryl sulfosuccinate; polyoxyethylene alkyl ether phosphates; polyoxyethylene alkyl ether acetates; etc. When the anionic surfactant forms a salt, the salt may be, for example, a metal salt (preferably a monovalent metal salt) such as sodium salt, potassium salt, calcium salt, magnesium salt, etc., an ammonium salt, an amine salt, etc.

[0051] Examples of non-reactive nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether and polyoxyethylene stearyl ether; polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monostearate, and polyoxyethylene sorbitan monolaurate; polyoxyethylene glyceryl ether fatty acid esters; polyoxyethylene-polyoxypropylene block copolymers; and the like.

[0052] As the reactive surfactant, those having a polymerizable (typically radically polymerizable) functional group can be preferably used. For example, a reactive surfactant having a structure in which a radically polymerizable functional group is introduced into the anionic surfactant or nonionic surfactant as described above can be used. The type of the radically polymerizable functional group is not particularly limited, and can be, for example, an alkenyl group, an acryloyl group, a methacryloyl group, a vinyl group, a vinyl ether group (vinyloxy group), an allyl ether group (allyloxy group), etc. Specific examples of the alkenyl group include a propenyl group and an isopropenyl group (CH2=C(CH3)-). The concept of the propenyl group here includes a 1-propenyl group (CH3-CH=CH-) and a 2-propenyl group (CH2=CH-CH2-; sometimes referred to as an allyl group).

[0053] Examples of anionic reactive surfactants include polyoxyethylene (allyloxymethyl) alkyl ether sulfate (e.g., ammonium salt), polyoxyethylene nonylpropenyl phenyl ether sulfate (e.g., ammonium salt), alkyl aryl sulfosuccinate (e.g., sodium salt), methacryloxy polyoxypropylene sulfate (e.g., sodium salt), polyoxyalkylene alkenyl ether sulfate (e.g., ammonium salt in which the end of the alkenyl group is an isopropenyl group), etc. When anionic reactive surfactants form salts, the salts may be, for example, metal salts such as sodium salts, or nonmetal salts such as ammonium salts or amine salts. Examples of the nonionic reactive surfactant include polyoxyethylene nonylpropenyl phenyl ether.

[0054] Commercially available reactive surfactants include those manufactured by Daiichi Kogyo Seiyaku Co., Ltd. under the trade names "Aqualon HS-05", "Aqualon HS-10", "Aqualon HS-1025", "Aqualon HS-20", "Aqualon KH-10", "Aqualon KH-1025", "Aqualon KH-05", "Aqualon BC-0515", "Aqualon BC-10", "Aqualon BC-1025", "Aqualon BC-20", "Aqualon BC-2020", "Aqualon RN-20", "Aqualon RN-30", "Aqualon RN-50", and Examples of such products include Aqualon AR-10, Aqualon AR-20, Aqualon AR-1025, and Aqualon AR-2020, ADEKA Corporation product names "ADEKA REASOAP SE-10N" and "ADEKA REASOAP SR-1025," Kao Corporation product names "Latemul PD-104," "Latemul PD-420," "Latemul PD-430," and "Latemul PD-450," Sanyo Chemical Industries, Ltd. product names "Eleminol JS-20" and "Eleminol RS-3000," and Nippon Nyukazai Co., Ltd. product name "Anthox MS-60."

[0055] From the viewpoint of emulsification performance and the like, in one embodiment, an anionic reactive surfactant can be preferably used. When a nonionic reactive surfactant is used, more preferable results can be achieved by using it in combination with another surfactant, for example, an anionic reactive surfactant, an anionic non-reactive surfactant, a nonionic non-reactive surfactant, etc.

[0056] The surfactant used in the technology disclosed herein preferably contains a reactive surfactant from the viewpoint of improving water resistance. In other words, at least a part of the surfactant used is preferably a reactive surfactant. By emulsion polymerizing the monomer raw material in the presence of the reactive surfactant, the reactive surfactant can react and be incorporated into the acrylic polymer. By incorporating the reactive surfactant into the acrylic polymer, the amount of free surfactant is reduced. This can improve water resistance. Therefore, performing polymerization using a reactive surfactant can be advantageous for achieving both polymerization stability and water resistance of the adhesive layer obtained from the adhesive composition containing the acrylic polymer after polymerization. From the viewpoint of achieving better water resistance, the proportion of the reactive surfactant in the total weight of the surfactant used during emulsion polymerization can be 50% by weight or more, more preferably 70% by weight or more, and for example, an embodiment in which only the reactive surfactant is used as the surfactant can be preferably adopted. In addition, the reactive surfactant incorporated into the acrylic polymer is restricted in its movement within the adhesive layer, so that it is less likely to bleed out to the surface of the adhesive layer. This can also favorably contribute to improving water resistance. In this specification, "containing a reactive surfactant" refers to a concept including the inclusion of the reactive surfactant in a state after its reactive functional group (e.g., radically polymerizable functional group) has reacted. The reactive surfactant in the technology disclosed herein is typically contained in the water-dispersed pressure-sensitive adhesive composition or pressure-sensitive adhesive layer in a form in which at least a portion of the surfactant is incorporated in the acrylic polymer as described above.

[0057] The weight average molecular weight (Mw) of the acrylic polymer is not particularly limited, and is, for example, 10×10 4 ~500×10 4Here, the Mw of the acrylic polymer refers to the Mw of the toluene-soluble portion (sol portion) of the acrylic polymer. The Mw of the acrylic polymer refers to a value calculated in terms of standard polystyrene based on GPC (gel permeation chromatography). From the viewpoint of improving the adhesive properties, the Mw of the acrylic polymer is preferably 150×10 4 Less than or equal to 100×10 4 From the viewpoint of cohesion and the like, the Mw of the acrylic polymer is preferably 20×10 4 More preferably, 30×10 4 or more (e.g. 40×10 4 or more).

[0058] (tackifier resin) The aqueous dispersion PSA composition disclosed herein contains a tackifier resin, which allows the production of a PSA sheet exhibiting excellent adhesive properties (e.g., adhesive strength, repulsion resistance).

[0059] The tackifier resin is a water-dispersed tackifier resin (also referred to as a tackifier resin emulsion). That is, the water-dispersed PSA composition disclosed herein contains the tackifier resin in the form of an emulsion in which the tackifier resin is dispersed in water. For example, by mixing an aqueous emulsion of an acrylic polymer with an emulsion of the tackifier resin, a PSA composition containing these components in a desired ratio can be easily prepared. It is preferable to use a tackifier resin emulsion that is substantially free of at least aromatic hydrocarbon solvents (more preferably, substantially free of aromatic hydrocarbon solvents and other organic solvents).

[0060] Examples of tackifying resins include rosin-based tackifying resins (including rosin derivative tackifying resins), petroleum-based tackifying resins, terpene-based tackifying resins, phenol-based tackifying resins, ketone-based tackifying resins, etc. These can be used alone or in combination of two or more.

[0061] Examples of the rosin-based tackifying resin include rosins such as gum rosin, wood rosin, and tall oil rosin, as well as stabilized rosins (e.g., stabilized rosins obtained by disproportionating or hydrogenating the rosins), polymerized rosins (e.g., polymers, typically dimers, of the rosins), and modified rosins (e.g., unsaturated acid-modified rosins modified with unsaturated acids such as maleic acid, fumaric acid, and (meth)acrylic acid). Examples of the rosin derivative tackifying resin include esters of the rosin-based resins (for example, rosin esters such as stabilized rosin ester and polymerized rosin ester), phenol-modified products of the rosin-based resins (phenol-modified rosin) and esters thereof (phenol-modified rosin ester). Examples of the petroleum-based tackifying resin include aliphatic petroleum resins, aromatic petroleum resins, copolymer petroleum resins, alicyclic petroleum resins, and hydrogenated versions of these. Examples of the terpene-based tackifying resin include α-pinene resin, β-pinene resin, aromatic modified terpene resin, and terpene phenol resin. Examples of the ketone-based tackifying resin include ketone-based resins obtained by condensation of ketones (e.g., aliphatic ketones such as methyl ethyl ketone, methyl isobutyl ketone, and acetophenone; alicyclic ketones such as cyclohexanone and methylcyclohexanone) with formaldehyde; and the like.

[0062] Examples of tackifier resins that can be preferably used in the technology disclosed herein include rosin-based tackifier resins and terpene-based tackifier resins. Suitable examples of rosin-based tackifier resins include stabilized rosin esters and polymerized rosin esters. Suitable examples of terpene-based tackifier resins include terpene phenol-based resins.

[0063] Such a tackifier resin emulsion may be prepared using a surfactant (emulsifier) ​​as necessary. The surfactant that can be used in the preparation of the tackifier resin emulsion may be one or more appropriately selected from the surfactants that can be used in the preparation of the acrylic polymer emulsion. Usually, an anionic surfactant or a nonionic surfactant is preferably used. The surfactant used in the preparation of the acrylic polymer emulsion and the surfactant used in the preparation of the tackifier resin emulsion may be the same or different. For example, an embodiment in which an anionic surfactant is used in the preparation of both emulsions, an embodiment in which a nonionic surfactant is used in both emulsions, an anionic surfactant in one emulsion and a nonionic surfactant in the other emulsion, etc., may be preferably adopted. The amount of the surfactant used is not particularly limited as long as it is an amount that can prepare the tackifier resin in the form of an emulsion, and may be, for example, about 0.2 parts by weight or more (preferably 0.5 parts by weight or more) relative to 100 parts by weight (based on solid content) of the tackifier resin, and may be about 10 parts by weight or less (preferably 5 parts by weight or less).

[0064] The softening point of the tackifier resin used is not particularly limited. From the viewpoint of improving cohesive strength, the softening point of the tackifier resin may be, for example, 80° C. or higher, preferably 90° C. or higher, 100° C. or higher, 120° C. or higher, or 130° C. or higher.

[0065] Although not particularly limited, in some embodiments, the tackifier resin in the technology disclosed herein may include a high-softening point tackifier resin having a softening point of 140°C or more. The softening point of the high-softening point tackifier resin is preferably 145°C or more, and may be, for example, 150°C or more, 155°C or more, 160°C or more, or 165°C or more. By using the high-softening point tackifier resin, both adhesion and cohesiveness can be suitably achieved. The upper limit of the softening point of the tackifier resin is not particularly limited, but from the viewpoint of compatibility, low-temperature characteristics, etc., it is usually appropriate that it is 200°C or less, preferably 180°C or less, and may be 175°C or less.

[0066] The softening point of the tackifier resin is defined as a value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is melted as quickly as possible at a low temperature, and is carefully filled into a ring placed on a flat metal plate, while taking care not to create bubbles. After cooling, the part that protrudes from the flat surface, including the top end of the ring, is cut off with a slightly heated knife. Next, a holder (ring stand) is placed in a glass container (heating bath) with a diameter of 85 mm or more and a height of 127 mm or more, and glycerin is poured to a depth of 90 mm or more. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) and the ring filled with the sample are immersed in glycerin without touching each other, and the temperature of the glycerin is kept at 20°C ± 5°C for 15 minutes. Next, the steel ball is placed in the center of the surface of the sample in the ring, and this is placed in a fixed position on the holder. Next, keeping the distance from the top of the ring to the glycerin surface at 50 mm, place a thermometer and align the center of the thermometer's mercury bulb to the same height as the center of the ring, then heat the container. The flame of the Bunsen burner used for heating should be midway between the center of the bottom of the container and its edge, and heating should be uniform. After heating begins and the temperature of the bath reaches 40°C, the rate of increase must be 5.0 ± 0.5°C per minute. The sample gradually softens and flows down the ring, and the temperature is read when it finally touches the bottom plate, and this is the softening point. The softening point is measured for two or more samples at the same time, and the average value is used.

[0067] The amount of the tackifier resin used (based on solid content) is usually 1 part by weight or more per 100 parts by weight of the acrylic polymer, from the viewpoint of optimally exerting the effect of use, and is preferably 3 parts by weight or more (e.g. 5 parts by weight or more), more preferably 12 parts by weight or more, and even more preferably 16 parts by weight or more. According to the technology disclosed herein, good water resistance can be realized even in an embodiment containing 22 parts by weight or more (e.g. 25 parts by weight or more) of the tackifier resin per 100 parts by weight of the acrylic polymer. In addition, from the viewpoint of cohesive strength, etc., the amount of the tackifier resin used is usually 90 parts by weight or less per 100 parts by weight of the acrylic polymer, and is preferably 70 parts by weight or less, more preferably 55 parts by weight or less, and even more preferably 50 parts by weight or less (e.g. 45 parts by weight or less, typically 40 parts by weight or less).

[0068] When the water-dispersed PSA composition disclosed herein contains a high softening point tackifier resin, only the high softening point tackifier resin may be used as the tackifier resin from the viewpoint of cohesive strength, etc. Also, from the viewpoint of balancing various adhesive properties, in some embodiments, a high softening point tackifier resin may be used in combination with a tackifier resin having a lower softening point (e.g., a tackifier resin having a softening point of 120°C or less, or 110°C or less). In such embodiments, the proportion of the high softening point tackifier resin in the total tackifier resin used may be, for example, 20% by weight or more, 40% by weight or more, or 60% by weight or more. The proportion of the high softening point tackifier resin may be, for example, 90% by weight or less, 80% by weight or less, or 70% by weight or less.

[0069] (alkali metal ions) The water-dispersed PSA composition disclosed herein contains an alkali metal ion. By incorporating an alkali metal ion into an acrylic water-dispersed PSA composition containing a water-dispersed tackifier resin, the water resistance of a PSA layer formed from the water-dispersed PSA composition can be improved. In a preferred embodiment, the alkali metal ion contained in the water-dispersed PSA composition is at least one of Na ions and K ions. By incorporating an appropriate amount of Na ions and / or K ions into an acrylic water-dispersed PSA composition containing a water-dispersed tackifier resin, the water resistance of a PSA layer formed from the composition can be effectively improved while suppressing aggregation of the composition.

[0070] The method for incorporating alkali metal ions into the water-dispersed pressure-sensitive adhesive composition disclosed herein is not particularly limited. For example, alkali metal ions can be incorporated into the water-dispersed pressure-sensitive adhesive composition by adding hydroxide, hydrochloride, sulfate, or the like of an alkali metal to the water-dispersed pressure-sensitive adhesive composition. From the viewpoint of suppressing aggregation of the water-dispersed pressure-sensitive adhesive composition, it is preferable to add an alkali metal hydroxide to the water-dispersed pressure-sensitive adhesive composition. In a preferred embodiment disclosed herein, the water-dispersed pressure-sensitive adhesive composition contains sodium hydroxide and / or potassium hydroxide.

[0071] The amount of alkali metal ions contained in the aqueous dispersion type pressure-sensitive adhesive composition (when the aqueous dispersion type pressure-sensitive adhesive composition contains two or more kinds of alkali metal ions, the total amount is not particularly limited). From the viewpoint of improving the water resistance of the pressure-sensitive adhesive layer, the amount of alkali metal ions contained in the aqueous dispersion type pressure-sensitive adhesive composition is preferably 0.001 parts by weight or more (for example, 0.002 parts by weight or more) relative to 100 parts by weight of the base polymer, more preferably 0.005 parts by weight or more, even more preferably 0.01 parts by weight or more, and particularly preferably 0.03 parts by weight or more. From the viewpoint of further improving the water resistance and suppressing the decrease in peel strength due to heating and humidification, the amount of alkali metal ions contained in the aqueous dispersion type pressure-sensitive adhesive composition is preferably 0.04 parts by weight or more, more preferably 0.05 parts by weight or more, relative to 100 parts by weight of the base polymer. From the viewpoints of inhibiting aggregation of the water-dispersed pressure-sensitive adhesive composition and inhibiting corrosion of metal adherends, the amount of alkali metal ions contained in the water-dispersed pressure-sensitive adhesive composition is preferably 1 part by weight or less (e.g., 0.5 parts by weight or less) per 100 parts by weight of the base polymer, more preferably 0.3 parts by weight or less, and even more preferably 0.2 parts by weight or less.

[0072] The content of alkali metal ions in the adhesive sheet (when the adhesive sheet contains two or more kinds of alkali metal ions, the total content) is not particularly limited. From the viewpoint of improving the water resistance of the adhesive layer, the content of alkali metal ions per 100 parts by weight of the adhesive sheet is preferably 0.1 parts by weight or more (for example, 0.2 parts by weight or more), more preferably 0.3 parts by weight or more, even more preferably 0.35 parts by weight or more, and particularly preferably 0.4 parts by weight or more. From the viewpoint of further improving the water resistance and suppressing the decrease in peel strength due to heating and humidification, the total content of alkali metal ions in the adhesive sheet is preferably 0.5 parts by weight or more, more preferably 0.6 parts by weight or more, and even more preferably 0.65 parts by weight or more, per 100 parts by weight of the adhesive sheet. From the viewpoint of suppressing the aggregation of the water-dispersed adhesive composition and the corrosion of the metal adherend, the content of alkali metal ions in the adhesive sheet is preferably 2 parts by weight or less (for example, 1.5 parts by weight or less), more preferably 1 part by weight or less, and even more preferably 0.8 parts by weight or less, per 100 parts by weight of the adhesive sheet.

[0073] Here, when the pressure-sensitive adhesive sheet used as the standard for the alkali metal ion content has a structure including a substrate and a pressure-sensitive adhesive layer, the pressure-sensitive adhesive sheet includes the pressure-sensitive adhesive layer and the substrate, but does not include a release liner. When the pressure-sensitive adhesive sheet is a substrate-less pressure-sensitive adhesive sheet, the pressure-sensitive adhesive sheet includes only the pressure-sensitive adhesive layer, but does not include a release liner. The content of the alkali metal ions in the pressure-sensitive adhesive sheet is measured by the method described in the Examples below.

[0074] (Crosslinking agent) The aqueous dispersion type PSA composition used to form the PSA layer preferably contains a crosslinking agent as an optional component. The PSA layer in the technology disclosed herein may contain the crosslinking agent in the form after crosslinking reaction, the form before crosslinking reaction, the form after partial crosslinking reaction, or an intermediate or composite form thereof. The crosslinking agent is typically contained in the PSA layer exclusively in the form after crosslinking reaction.

[0075] The type of crosslinking agent is not particularly limited, and may be appropriately selected from, for example, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, hydrazine-based crosslinking agents, amine-based crosslinking agents, and the like. As the crosslinking agent used here, either oil-soluble or water-soluble may be used. The crosslinking agent may be used alone or in combination of two or more kinds. The amount of the crosslinking agent used is not particularly limited, and for example, it is appropriate to use about 10 parts by weight or less (for example, about 0.005 to 10 parts by weight) relative to 100 parts by weight of the acrylic polymer, and preferably about 5 parts by weight or less (0.01 to 5 parts by weight).

[0076] (Other added ingredients) In addition, the water-dispersed pressure-sensitive adhesive composition disclosed herein preferably contains a silicon compound (typically a silane coupling agent) from the viewpoint of easy releasability from a release liner. As the silicon compound, one or more of alkylalkoxysilane compounds, vinyl group-containing silane compounds, epoxy group-containing silane compounds, styryl group-containing silane compounds, (meth)acryloyl group-containing silane compounds, amino group-containing silane compounds, ureido group-containing silane compounds, mercapto group-containing silane compounds, isocyanate group-containing silane compounds, and silyl group-containing sulfides can be used. Among them, alkylalkoxysilane compounds are preferred. The molecular weight of the silicon compound is suitably about 100 or more (e.g., 200 or more), and may be about 500 or less (e.g., 350 or less).

[0077] As the alkylalkoxysilane compound, any of alkyltrialkoxysilane, dialkyldialkoxysilane, trialkylmonoalkoxysilane, tetraalkoxysilane, and phenylalkoxysilane can be used. The alkyl includes chain and cyclic. Specific examples of the above compounds include methyltrimethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltrimethoxysilane, n-decyltrimethoxysilane, hexadecyltrimethoxysilane, methyltriethoxysilane, dimethoxydimethylsilane, diethoxydimethylsilane, cyclohexylmethyldimethoxysilane, methoxytrimethylsilane, octadecyldimethylmethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethoxydiphenylsilane, diphenylethoxymethylsilane, and dimethoxymethylphenylsilane. Among them, alkyltrialkoxysilane is preferred.

[0078] The content of the silicon compound is preferably 0.005 parts by weight or more (e.g., 0.01 parts by weight or more, typically 0.03 parts by weight or more) relative to 100 parts by weight of the acrylic polymer in order to fully exert the effect of adding the silicon compound. Also, from the viewpoint of storage stability, the content of the silicon compound is preferably less than 1.0 part by weight (e.g., 0.5 parts by weight or less, typically 0.3 parts by weight or less) relative to 100 parts by weight of the acrylic polymer.

[0079] The adhesive composition disclosed herein may contain an acid or base (such as aqueous ammonia) used for the purpose of adjusting pH, etc., as necessary. Examples of other optional components that may be blended into the adhesive composition disclosed herein include viscosity modifiers, leveling agents, crosslinking assistants, release modifiers, plasticizers, softeners, fillers, colorants (pigments, dyes, etc.), antistatic agents, antioxidants, UV absorbers, antioxidants, light stabilizers, etc. As for such various additives, those that are conventionally known can be used in the usual manner, and they do not particularly characterize the present invention, so detailed explanations will be omitted.

[0080] <Adhesive sheet> (Example of adhesive sheet structure) The pressure-sensitive adhesive sheet disclosed herein comprises a pressure-sensitive adhesive layer formed using the above-mentioned water-dispersed pressure-sensitive adhesive composition. It may be a substrate-attached pressure-sensitive adhesive sheet having such a pressure-sensitive adhesive layer on one or both sides of a substrate (support), or may be a substrate-less pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer held on a release liner (which may also be understood as a substrate having a release surface). The concept of the pressure-sensitive adhesive sheet referred to here may include those called pressure-sensitive adhesive tape, pressure-sensitive adhesive label, pressure-sensitive adhesive film, etc. The pressure-sensitive adhesive layer is typically formed continuously, but is not limited to such a form, and may be a pressure-sensitive adhesive layer formed in a regular or random pattern such as a dotted or striped pattern. The pressure-sensitive adhesive sheet may be in the form of a roll or a sheet. Alternatively, it may be a pressure-sensitive adhesive sheet processed into various shapes.

[0081] The pressure-sensitive adhesive sheet disclosed herein may be in the form of a double-sided pressure-sensitive adhesive sheet having a cross-sectional structure as shown, for example, in FIG. 1. The pressure-sensitive adhesive sheet 1 includes a substrate 15 and a first pressure-sensitive adhesive layer 11 and a second pressure-sensitive adhesive layer 12 supported on both sides of the substrate 15. More specifically, the first pressure-sensitive adhesive layer 11 and the second pressure-sensitive adhesive layer 12 are provided on a first surface 15A and a second surface 15B (both of which are non-releasable) of the substrate 15, respectively. Before use (before attachment to an adherend), the double-sided pressure-sensitive adhesive sheet 1 may be in a form in which the front surface 21A and the back surface 21B are both release surfaces and the sheet is wound in a spiral shape, as shown in FIG. 1. In the double-sided pressure-sensitive adhesive sheet 1 in this form, the surface of the second pressure-sensitive adhesive layer 12 (second pressure-sensitive adhesive surface 12A) is protected by the front surface 21A of the release liner 21, and the surface of the first pressure-sensitive adhesive layer 11 (first pressure-sensitive adhesive surface 11A) is protected by the back surface 21B of the release liner 21. Alternatively, first adhesive surface 11A and second adhesive surface 12A may be protected by two independent release liners, respectively.

[0082] (Characteristics of adhesive sheet) The adhesive strength of the pressure-sensitive adhesive sheet (typically a double-sided pressure-sensitive adhesive sheet) disclosed herein is not particularly limited. The pressure-sensitive adhesive sheet according to a preferred embodiment may have a 180-degree peel strength (peeling strength from SUS plate) of, for example, 5 N / 20 mm or more after being attached to a stainless steel plate and kept under conditions of 23° C. and 50% RH for 30 minutes. Hereinafter, the peel strength from SUS plate after being kept under conditions of 23° C. and 50% RH for 30 minutes is also referred to as the "initial peel strength S0". A pressure-sensitive adhesive sheet exhibiting such characteristics is preferably used as a strong adhesive pressure-sensitive adhesive sheet that firmly fixes an article or member. The initial peel strength S0 is more preferably 10 N / 20 mm or more, and even more preferably 12 N / 20 mm or more (for example, 14 N / 20 mm or more, or even 15 N / 20 mm or more). When the pressure-sensitive adhesive sheet disclosed herein is a double-sided pressure-sensitive adhesive sheet, it is preferable that both adhesive surfaces exhibit the above peel strength.

[0083] According to the technology disclosed herein, a pressure-sensitive adhesive sheet with improved water resistance can be realized. The pressure-sensitive adhesive sheet according to a preferred embodiment can have a 180-degree peel strength (peel strength from SUS plate) of, for example, 4N / 20mm or more after being attached to a stainless steel plate and kept for 24 hours under conditions of 60°C and 95% RH (hereinafter also referred to as heated and humidified conditions). Hereinafter, the peel strength from SUS plate after being kept for 24 hours under the above-mentioned heated and humidified conditions is also referred to as "peel strength Sw after heating and humidification". A pressure-sensitive adhesive sheet exhibiting such characteristics can achieve highly reliable bonding even in a humid environment (typically a high-temperature and humid environment). For this reason, it can be preferably used as a pressure-sensitive adhesive sheet with high adhesive reliability. For example, it can be preferably used as a pressure-sensitive adhesive sheet that exhibits high adhesive reliability even in an environment where humidity may increase (for example, an environment where it may be exposed to an atmosphere where humidity changes, etc.). The post-heating and humidifying peel strength Sw is more preferably 5 N / 20 mm or more, and even more preferably 8 N / 20 mm or more (e.g., 10 N / 20 mm or more, or even 11 N / 20 mm or more). When the pressure-sensitive adhesive sheet disclosed herein is a double-sided pressure-sensitive adhesive sheet, it is preferable that both adhesive surfaces exhibit the above peel strength.

[0084] The peel strengths S0 and Sw are measured by the method described in the examples below.

[0085] In the pressure-sensitive adhesive sheet disclosed herein, the retention ratio, which is the ratio of the peel strength Sw after heating and humidification to the initial peel strength S0, is not particularly limited. The retention ratio (Sw / S0) may be, for example, 0.25 or more. In some embodiments, the retention ratio (Sw / S0) is preferably 0.3 or more, more preferably 0.4 or more, even more preferably 0.5 or more, and particularly preferably 0.6 or more (e.g., 0.65 or more). In some preferred embodiments, the retention ratio (Sw / S0) may be 0.7 or more, 0.8 or more, or 0.9 or more. The upper limit of the retention ratio (Sw / S0) is not particularly limited.

[0086] The total thickness of the adhesive sheet disclosed herein is not particularly limited. The total thickness of the adhesive sheet may be, for example, 1 mm or less (e.g., 500 μm or less). Here, the total thickness of the adhesive sheet refers to the total thickness of the substrate and the adhesive layer. In a preferred embodiment, the total thickness may be 300 μm or less (more preferably 200 μm or less). The lower limit of the total thickness of the adhesive sheet may be, for example, 30 μm or more, and is usually 50 μm or more, preferably 70 μm or more, more preferably 100 μm or more (e.g., 120 μm or more).

[0087] <Adhesive layer> The adhesive layer in the technology disclosed herein can be suitably formed by applying the above-mentioned water-dispersed adhesive composition to a predetermined surface and drying or curing it. When applying (typically applying) the adhesive composition, a conventional coater (e.g., gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, spray coater, etc.) can be used. The thickness of the adhesive layer is not particularly limited, and is usually about 2 μm or more, preferably about 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more (typically 30 μm or more, for example 50 μm or more). The thickness of the adhesive layer is usually about 200 μm or less, and preferably about 120 μm or less (e.g. 100 μm or less, typically 80 μm or less).

[0088] <Base material> In the adhesive sheet disclosed herein, examples of the substrate supporting (backing) the adhesive layer include polyolefin (polyethylene, polypropylene, ethylene-propylene copolymer, etc.) films, polyester (polyethylene terephthalate, etc.) films, vinyl chloride resin films, vinyl acetate resin films, polyimide resin films, polyamide resin films, fluorine resin films, and other plastic films such as cellophane; Japanese paper, craft paper, glassine paper, wood-free paper, synthetic paper, topcoat paper, and other papers; woven fabrics and nonwoven fabrics made by spinning various fibrous materials alone or in combination; rubber sheets made of natural rubber, butyl rubber, and the like; foam sheets made of foams such as polyurethane foam and polychloroprene rubber foam; metal foils such as aluminum foil and copper foil; and composites thereof. The plastic films may be of a non-stretched type or of a stretched type (uniaxially stretched type or biaxially stretched type). The substrate may have a single layer form or a laminated form.

[0089] As a preferred embodiment of the substrate, a nonwoven fabric substrate is used. For example, any of the following can be used: nonwoven fabric made of natural fibers such as wood pulp, cotton, and hemp (e.g., Manila hemp); nonwoven fabric made of chemical fibers (synthetic fibers) such as polyester fibers, rayon, vinylon, acetate fibers, polyvinyl alcohol (PVA) fibers, polyamide fibers, polyolefin fibers, and polyurethane fibers; and nonwoven fabric made by combining two or more types of fibers of different materials. Among them, a nonwoven fabric substrate made of hemp (e.g., Manila hemp) is preferred. In this case, the amount of hemp contained in the nonwoven fabric is preferably 90% by weight or more, more preferably 95% by weight or more. Particularly preferably, a nonwoven fabric made substantially only of hemp is used.

[0090] When nonwoven fabric is used as the substrate, the basis weight is approximately 10 g / m 2 or more (e.g. 13g / m 2 or more), and is approximately 25 g / m 2 Less than (e.g. 22g / m 2The nonwoven fabric preferably has a bulk density of about 0.25 g / cm3 or less (which can be calculated by dividing the basis weight by the thickness). 3 ~0.50g / cm 3 It is preferable that the nonwoven fabric has a tensile strength in both the machine direction (MD) and the transverse direction (TD) of about 8 N / 15 mm or more, more preferably at least an MD tensile strength of 12 N / 15 mm or more (e.g., 18 N / 15 mm or more, or even 24 N / 15 mm or more), and even more preferably both an MD and TD tensile strength of about 12 N / 15 mm or more (e.g., 16 N / 15 mm or more). A nonwoven fabric satisfying such a tensile strength is suitable for forming an adhesive sheet with excellent tensile strength.

[0091] In addition, in the manufacturing stage of the nonwoven fabric, polymers such as viscose, starch, cationic polymers (e.g., polyamide, amine, epichlorohydrin) may be used for the purpose of improving the strength (e.g., tensile strength) of the nonwoven fabric. Such polymers (which can be understood as strength improvers for the nonwoven fabric) may be added at the papermaking stage of the nonwoven fabric (the stage of accumulating fibers), or may be applied or impregnated after papermaking. Nonwoven fabrics made using such strength improvers are suitable for forming pressure-sensitive adhesive sheets with excellent tensile strength. Therefore, for example, in double-sided pressure-sensitive adhesive sheets that are attached to recycled parts, the use of nonwoven fabrics made using the above-mentioned strength improvers is particularly effective.

[0092] The substrate may contain various additives such as fillers (inorganic fillers, organic fillers, etc.), antioxidants, antioxidants, UV absorbers, antistatic agents, lubricants, plasticizers, colorants (pigments, dyes, etc.), etc., as necessary. The surface of the substrate (particularly the surface on which the adhesive layer is provided) may be subjected to a known or conventional surface treatment such as a corona discharge treatment, a plasma treatment, or application of a primer. Such a surface treatment may be, for example, a treatment for enhancing the substrate anchoring ability of the adhesive layer.

[0093] The thickness of the substrate can be appropriately selected depending on the purpose, but is about 10 μm or more, usually 20 μm or more, preferably 30 μm or more (typically 40 μm or more, for example 50 μm or more). Increasing the thickness of the substrate increases the strength of the substrate or adhesive sheet, and tends to improve the handling (processability) during production or use. The thickness is about 800 μm or less, usually 450 μm or less, preferably 300 μm or less (typically 150 μm or less, for example 100 μm or less). Limiting the thickness of the substrate tends to improve the ability to follow the surface shape (steps, etc.) of the adherend.

[0094] <Release liner> The release liner (which may have both the functions of protection and support) that protects or supports the adhesive layer is not particularly limited in its material or structure, and an appropriate one can be selected from known release liners. For example, a release liner having a structure in which at least one surface of the substrate is subjected to a release treatment (typically, a release treatment layer made of a release treatment agent is provided) can be suitably used. As the substrate (subject to release treatment) that constitutes this type of release liner, the same substrate as that described above as the substrate that constitutes the adhesive sheet (various plastic films, papers, cloths, rubber sheets, foam sheets, metal foils, composites thereof, etc.) can be appropriately selected and used. As the release treatment agent that forms the release treatment layer, a known or conventional release treatment agent (for example, a silicone-based, fluorine-based, long-chain alkyl-based, etc. release treatment agent) can be used. Alternatively, a low-adhesion substrate made of a fluorine-based polymer (e.g., polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.) or a low-polarity polymer (e.g., an olefin resin such as polyethylene or polypropylene, etc.) may be used as a release liner without subjecting the surface of the substrate to a release treatment. Alternatively, such a low-adhesion substrate may be subjected to a release treatment on its surface and used as a release liner.

[0095] The thickness of the substrate and release treatment layer constituting the release liner are not particularly limited and can be appropriately selected depending on the purpose, etc. The total thickness of the release liner (the total thickness including the substrate and release treatment layer in a release liner having a substrate surface with a release treatment layer) is preferably, for example, about 15 μm or more (typically about 15 μm to 500 μm), and more preferably about 25 μm to 500 μm.

[0096] <Method of manufacturing a substrate-attached double-sided pressure-sensitive adhesive sheet> In the preparation of a double-sided pressure-sensitive adhesive sheet with a substrate, the method of providing a pressure-sensitive adhesive layer on one side and the other side of the substrate is not particularly limited. Usually, it is preferable to apply any one of the following methods to each of the one side and the other side: (1) a method of applying (typically applying) a water-dispersed pressure-sensitive adhesive composition to a release liner and drying the composition to form a pressure-sensitive adhesive layer on the release liner, and then attaching the pressure-sensitive adhesive layer to the substrate to transfer (laminate) the composition (hereinafter also referred to as a "transfer method"); and (2) a method of applying (typically applying) a water-dispersed pressure-sensitive adhesive composition directly to a substrate and drying the composition (hereinafter also referred to as a "direct application method" or "direct method"). For example, the transfer method may be applied to both sides of the substrate to produce a double-sided pressure-sensitive adhesive sheet (transfer-transfer method), or the transfer method may be applied to one side of the substrate (typically the side on which the pressure-sensitive adhesive layer is first provided) and the direct application method may be applied to the other side to produce a double-sided pressure-sensitive adhesive sheet (transfer-direct method).

[0097] <Application> The adhesive sheet disclosed herein can easily maintain its adhesive strength (peel strength) to the adherend even when exposed to a high-temperature and high-humidity environment after being attached to the adherend. Taking advantage of such characteristics, the adhesive sheet disclosed herein can be preferably used for various products that can be used in environments requiring water resistance or moisture resistance, or for fixing, joining, forming, decorating, protecting, supporting, etc. of the products or the components in a form attached to the components constituting the products. In particular, it can be preferably used for fixing the products or the components. Examples of environments requiring water resistance or moisture resistance include environments where temperature and humidity change significantly (for example, water areas in homes, outdoors where exposed to rain and wind, etc.). Examples of the products include home appliances, office automation equipment, vehicles (for example, automobiles), home equipment (including furniture and furnishings), mobile devices, etc.

[0098] Examples of home appliances include televisions (CRT, LCD, plasma, OLED, etc.), DVD players and other AV equipment, microwave ovens, rice cookers, washing machines, washer-dryers, vacuum cleaners, refrigerators, freezers, pots, air conditioners, dishwashers, air purifiers, lighting equipment, clocks, thermometers, PDAs (personal digital assistance), landline telephones, etc. Examples of office automation equipment include word processors, electronic dictionaries, desktop computers, notebook computers, CRT displays, LCD displays, OLED displays, printers, scanners, copy machines, fax machines, and multifunction machines that have two or more of these functions. Examples of vehicles include automobiles and trains. Examples of home equipment (including furniture and furnishings) include baths, vanities, toilets, cupboards, bookshelves, tables, dressers, window glass, etc. Examples of portable devices include mobile phones, smartphones, tablet computers, notebook computers, various wearable devices, digital cameras, digital video cameras, audio equipment (portable music players, IC recorders, etc.), calculators (calculators, etc.), portable game devices, electronic dictionaries, electronic organizers, e-books, in-car information equipment, portable radios, portable televisions, portable printers, portable scanners, portable modems, and other portable electronic devices, as well as mechanical wristwatches, pocket watches, flashlights, hand mirrors, etc. EXAMPLES

[0099] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples. In the following description, "parts" and "%" are by weight unless otherwise specified.

[0100] <Example 1> (Preparation of Acrylic Polymer A) In a reaction vessel equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser, 0.09 parts of a reactive surfactant (trade name "Aqualon KH-1025", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 67 parts of distilled water were added, and the atmosphere was replaced with nitrogen at room temperature (25°C) for 1 hour while stirring. The temperature was then raised to 60°C, and 0.10 parts of a polymerization initiator (trade name "VA-057", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added, and the mixture was stirred for 5 minutes. Here, 85 parts of 2-ethylhexyl acrylate (2EHA), 13 parts of methyl acrylate (MA), 1.25 parts of acrylic acid (AA), 0.75 parts of methacrylic acid (MAA), 0.025 parts of t-dodecanethiol (chain transfer agent), 0.02 parts of 3-methacryloxypropyltrimethoxysilane (trade name "KBM-503", manufactured by Shin-Etsu Chemical Co., Ltd.) and 1.91 parts of a reactive surfactant (trade name "Aqualon KH-1025", manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) emulsified with 33 parts of distilled water were added dropwise over 4 hours and polymerized at 60 ° C. After aging at 70 ° C. for 1 hour, 0.05 parts of a polymerization initiator (trade name "VA-057", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added and aged for another 2 hours. The mixture was cooled to room temperature and adjusted to pH = 6 using 10% ammonia water as a pH adjuster to prepare acrylic polymer A.

[0101] (Preparation of adhesive sheet) To 100 parts of the solid content of acrylic polymer A, 30 parts of polymerized rosin ester (trade name "Super Ester E-865NT", manufactured by Arakawa Chemical Industries Co., Ltd., softening point 160°C) as a tackifier resin, 0.8 parts of thickener (trade name "Aron B-500", manufactured by Toagosei Co., Ltd.), and 0.7 parts of 10% aqueous sodium hydroxide solution were added, stirred, degassed, and applied to a release liner to a thickness of 60 μm after drying. This was applied to a nonwoven fabric (trade name "SP-14K", pulp-based nonwoven fabric manufactured by Daifuku Paper Co., Ltd., basis weight 14 g / m 2 ) to obtain a double-sided PSA sheet according to this example.

[0102] <Example 2, Example 4> A double-sided pressure-sensitive adhesive sheet according to this example was obtained in the same manner as in Example 1, except that the amount of 10% aqueous sodium hydroxide solution added relative to 100 parts of solids of acrylic polymer A was changed as shown in Table 1.

[0103] <Example 3> A double-sided PSA sheet according to this example was obtained in the same manner as in Example 1, except that a 10% aqueous solution of potassium hydroxide was used instead of the 10% aqueous solution of sodium hydroxide.

[0104] <Example 5> A double-sided PSA sheet according to this example was obtained in the same manner as in Example 1, except that the 10% aqueous sodium hydroxide solution was not added.

[0105] [Na ion and / or K ion content] As a sample, about 100 mg of adhesive sheet was weighed into a Teflon (registered trademark) container, acid was added, the container was sealed, and the container was placed in a microwave decomposition device (manufactured by CEM, product name "MARS5"), and microwaves were irradiated to perform pressure acid decomposition under a temperature condition not exceeding 220 ° C. Here, the above-mentioned adhesive sheet includes an adhesive layer and a substrate, but does not include a release liner. When the above-mentioned adhesive sheet is a substrate-less adhesive sheet, the above-mentioned adhesive sheet includes only an adhesive layer. After the pressure acid decomposition of the adhesive sheet, ultrapure water was added to make a constant volume of 50 mL, and quantitative analysis of Na ions and / or K ions was performed by inductively coupled plasma mass spectrometry (ICP-MS method) using an apparatus (manufactured by Agilent Technologies, product name "Agilent 7500cs"). The weight of the obtained Na ions and / or K ions was converted into the content of Na ions and / or K ions per 100 parts by weight of the adhesive sheet, and the results are shown in the corresponding columns of Table 1. The total content of Na ions and K ions was also calculated, and the results are shown in the corresponding columns in Table 1.

[0106] [Peeling strength against SUS plate] (Initial peel strength S0) The peel strength of the adhesive sheet from each example to the SUS plate was measured as follows. That is, the release liner covering one side of the adhesive sheet (double-sided adhesive sheet) was peeled off, and the sheet was backed by attaching it to a polyethylene terephthalate (PET) film having a thickness of 25 μm. The backed adhesive sheet was cut to a size of 20 mm in width and 100 mm in length to prepare a sample piece. In an environment of 23°C and 50% RH, the test piece was pressed against a stainless steel plate (SUS304BA plate) as an adherend by reciprocating a 2 kg roller once. After keeping the test piece in an environment of 23°C and 50% RH for 30 minutes, the 180° peel strength [N / 20 mm] was measured using a tensile tester at a tensile speed of 300 mm / min according to JIS Z0237. The measurement was performed three times (i.e., N=3), and the average value was taken as the initial peel strength S0 of the adhesive sheet. The results are shown in the corresponding columns in Table 1. When measurements are performed using a single-sided PSA sheet, the backing with a film may be omitted.

[0107] (Peel strength after heating and humidification Sw) The test piece was pressure-bonded to a stainless steel plate (SUS304BA plate) in the same manner as in the measurement of the initial peel strength S0. This was kept under heated and humidified conditions of 60°C and 95% RH for 24 hours. Next, the test piece was transferred to an environment of 23°C and 50% RH, and within 10 minutes, the 180° peel strength [N / 20mm] was measured in the same manner as in the measurement of the initial peel strength S0. The average value of three measurements was taken as the peel strength Sw of the pressure-sensitive adhesive sheet after heating and humidification. The maintenance rate (Sw / S0) was also calculated for each pressure-sensitive adhesive sheet. The results are shown in the corresponding columns in Table 1.

[0108] [Table 1]

[0109] As shown in Table 1, the pressure-sensitive adhesive sheets of Examples 1 to 4, which used pressure-sensitive adhesive compositions to which an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution was added, exhibited higher post-heating and humidifying peel strengths Sw than Example 5, which did not contain either an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution. In particular, the pressure-sensitive adhesive sheets of Examples 1 to 3, in which the total content of Na ions and K ions per 100 parts by weight of the pressure-sensitive adhesive sheet was equal to or greater than a predetermined amount, exhibited clearly superior post-heating and humidifying peel strengths Sw and also had high retention rates (Sw / S0) compared to the pressure-sensitive adhesive sheets of Examples 4 and 5. These results demonstrated that the pressure-sensitive adhesive sheets of Examples 1 to 3 have particularly excellent water resistance.

[0110] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]

[0111] 1 Adhesive sheet 11 First adhesive layer 11A 1st adhesive side 12 Second adhesive layer 12A 2nd adhesive side 15 Base material (support) 21 Release Liner

Claims

1. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from a water-dispersible pressure-sensitive adhesive composition, The water-dispersible PSA composition comprises an acrylic polymer as a base polymer, a water-dispersible tackifier resin, and at least one of Na ions and K ions, the total amount of Na ions and K ions contained in the pressure-sensitive adhesive sheet is 0.5 parts by weight or more and 0.8 parts by weight or less per 100 parts by weight of the pressure-sensitive adhesive sheet, The content of the water-dispersible tackifier resin is 25 parts by weight or more and 70 parts by weight or less based on 100 parts by weight of the base polymer, The pressure-sensitive adhesive sheet has a 180-degree peel strength after being attached to a stainless steel plate and held at 60°C and 95% RH for 24 hours that is 0.8 times or more the 180-degree peel strength after being attached to a stainless steel plate and held at 23°C and 50% RH for 30 minutes.

2. The pressure-sensitive adhesive sheet according to claim 1 , wherein the acrylic polymer is a polymer of a monomer raw material containing more than 50% by weight of alkyl (meth)acrylate.

3. The pressure-sensitive adhesive sheet according to claim 1 , wherein the aqueous dispersion-type pressure-sensitive adhesive composition further comprises a surfactant.

4. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein the water-dispersible pressure-sensitive adhesive composition contains, as the water-dispersible tackifier resin, a tackifier resin having a softening point of 90°C or higher.

5. The pressure-sensitive adhesive sheet according to any one of claims 1 to 4, which has a 180 degree peel strength of 4 N / 20 mm or more after being attached to a stainless steel plate and held under conditions of 60°C and 95% RH for 24 hours.

6. The pressure-sensitive adhesive sheet according to any one of claims 1 to 5, which is configured as a double-sided pressure-sensitive adhesive sheet including a substrate and, as the pressure-sensitive adhesive layers, a first pressure-sensitive adhesive layer disposed on one surface of the substrate and a second pressure-sensitive adhesive layer disposed on the other surface of the substrate.

7. The pressure-sensitive adhesive sheet according to claim 6 , wherein the substrate is a nonwoven fabric.

Citation Information

Patent Citations

  • Acrylic water-based pressure-sensitive adhesive composition

    JP2001055550A

  • Water dispersion acrylic adhesive tape or sheet for transporting electronic component

    JP2008285221A

  • Double-sided adhesive sheet

    JP2011016943A

  • Aqueous adhesive composition and utilization thereof

    JP2017132993A